Gender, nutritional status and disability-free life expectancy among older people in Santiago, Chile - Moreno, Ximena (PLoS One, 2018)
BACKGROUND: This study was aimed to estimate life expectancy (LE), disability-free life expectancy (DFLE) and disabled life expectancy (DLE) among older adults from Santiago, Chile, and to determine the existence of differences by gender and by body mass index (BMI) categories in these indicators. METHODS: A sample of 1216 people aged 60 or more, from the Chilean cohort of the Study of Health, Ageing and Well-Being was recruited in 2000; two follow-up assessments were carried out in a 10-year period. Functional limitation was assessed through self-report of difficulties in activities of daily living, instrumental activities of daily living and mobility. BMI was determined with measured weight and height. Multistate life tables were employed to estimate LE and healthy life expectancy (HLE). RESULTS: At 60 years, women could expect to live on average an additional 20.4 years (95% CI 19.0–21.6), and men an additional 16.4 years (95% CI 14.9–17.7). Total LE was longer among women at all ages, but they had a higher proportion of disabled years to be lived compared to men, with a difference of 14% at 60 years, and 10% at 90 years. There were no significant differences in LE, DFLE and DLE between BMI categories. DISCUSSION: Despite a longer LE, Chilean older women expect to live a higher proportion of years with disabilities, compared to men. Public health programs should address factors affecting LE of older men, and those associated with disability among older women.